The Use of Linguistic Features in Indonesian Students’ Texts at Hungarian Universities - Subandowo, Dedy (Central European Journal of Educational Research, 2022)
Students enrolled in a higher level of education may face challenges in producing assignments, including writing an essay. They need to present appropriate linguistic features in the text to demonstrate their writing quality. Comparing linguistic features during university study is one fundamental aspect of administering writing quality and showing student writing development. The topic presented in this study describes an initial statistical analysis and the frequency of linguistic features in the texts produced by Indonesian graduate students enrolled at Hungarian universities. This study proposed two research questions: 1) How frequently do pre-selected linguistic features appear in the texts of Indonesian graduate students? 2) How do these features appear in a paired T-test statistical analysis? Seven MSc and MA graduate students took part in the study to meet the goal. They are students at three different universities in Hungary, which all have a Social Science Faculty. During their second-year studies, fourteen essays with a minimum text length of 2000 words were collected. The findings revealed an increase in conjunctions, adjectives, abstract nouns, concrete nouns, noun phrases, expanded noun phrases, active verbs, verb phrases, and passive forms. Meanwhile, the frequency of linguistic features such as prepositions, definite articles, indefinite articles, noun clauses, adverbial clauses, and adjective clauses decreased. In addition, both the rise of nine linguistic features and the decrease of six features in the second semester are not statistically significant.